A 3D Finite Element Analysis of Bone Tissue in 3-Unit Implant-Supported Prostheses: Effect of Splinting Factor and Implant Length and Diameter - de Souza Batista, V. E.; Verri, F. R. [UNESP]; Lemos, C. A.; Cruz, R. S. [UNESP]; Noritomi, P. Y.; Pellizzer, E. P. [UNESP] (My University, 2021)
This study aimed to assess the effects of splinting in 3-unit implant-supported prostheses with varying the splinting factor, length of the implant, and the diameter of the 1°molar (1°M) implant on cortical bone tissue (CBT). Twelve 3D models were simulated, which represented the posterior maxillary with 3 implants, supporting 3-unit FDP varying the splinting factor (single-unit crowns, splinted crowns straight-line and offset implant configuration [OIC]), length of the implant (7mm and 8,5mm), and the diameter of the 1°M (Ø4 mm and Ø5 mm). The CBT was analyzed by maximum principal stress and microstrain maps. The increase in implant diameter improved the biomechanical behavior of rehabilitation. The increase of the implant diameter in the 1°M associated with OIC generated the best biomechanical behavior for CBT. The splinting was effective in decreasing stress and microstrain, mainly when associated with OIC and implant diameter of Ø5 in the 1°M. The effect of increasing the diameter of the implant referring to the 1°M for single-unit crowns was more effective than the effect of the splinting of implants with Ø4 mm in straight-line. The diameter and splinting factors showed to be more important than implant length to reduce the stress and microstrain on CBT.
Keywords: Dental Implant; Dental Prosthesis; Finite Element Analysis